Determinants of Poverty in East Java During The COVID-19 Pandemic - Dewi, Ima Sartika; Nursiyono, Joko Ade (EkBis: Jurnal Ekonomi dan Bisnis, 2023)
The global COVID-19 pandemic has infected million people in Indonesia. East Java has experienced Indonesia’s epicentre of positive COVID-19 cases. The economic disruption in East Java due to COVID-19 pandemic has led to increase the number of poor people. This study aims to examine the determinants of poverty during the pandemic outbreak. In this study, we employed multiple linear regression. The results reveals that simultaneously the cumulative number of COVID-19, unemployment rate, Gini Ratio, population density, human development index (HDI), and GRDP per capita affect the risk of poverty in East Java. Partially, the cumulative number of COVID-19, unemployment rate, population density, and HDI shows a significant effect to poverty. While the Gini ratio and GRDP per capita has an insignificant effect. The increase on cumulative number of COVID-19 cases is likely to increase the risk of poverty. Similarly, unemployment has a positive significant affect on poverty. The increase on unemployment rate tends to increase the number of poor people. Contrary, the HDI and population density have a negatively significant effect to poverty. The increase on HDI and population density tends to increase the number of poor people.